Pengaruh Penerapan Model Pembelajaran Direct Instruction terhadap Hasil Belajar PAI dan Budi Pekerti Siswa Kelas X SMAN 15 Padang - Hidayat, Rahma Gusti; Wirdati, Wirdati (TSAQOFAH, 2025)
This study is motivated by the limited research on the effectiveness of the Direct Instruction model in Islamic Religious Education (PAI), despite its potential to significantly impact students’ cognitive learning outcomes at the senior high school level. The research aims to analyze the effect of implementing the Direct Instruction model on student learning outcomes in PAI and Budi Pekerti for Grade X Phase E at SMA Negeri 15 Padang. A quantitative approach was employed using a quasi-experimental design, involving 71 students divided into experimental and control groups through purposive sampling. Data were collected using test instruments in the form of pretests and posttests, along with teacher questionnaires, and analyzed using the non-parametric Mann-Whitney U test due to non-normal data distribution. The findings indicate a significant effect of the Direct Instruction model on improving students’ cognitive learning outcomes. These results support Rosenshine’s theory, which emphasizes the importance of explicit and systematic instruction in enhancing conceptual understanding. The study concludes that implementing structured instructional models such as Direct Instruction can improve student achievement, particularly in the subject of Islamic Cultural History. The implications include reinforcing the academic literature on the model’s effectiveness in PAI learning contexts and offering practical recommendations for teachers and schools to adopt instructional strategies aligned with the characteristics of the subject matter and learners.